Queering Discourses of Urban Decline: Representing Montréal's Post-World War II "Lower Main" - Podmore, Julie (Historical Geography, 2015)
In this paper, I examine how urban redevelopment and the regulation of public spaces in Montréal in the 1960s transformed the representations of the Lower Main, the city’s historic red-light and entertainment district. I argue that although the Lower Main had long been central to anti-urban discourses regarding heterosexual prostitution, by the 1960s the increased regulation of the city’s queer and trans populations changed its meaning as a representation of the inner city in decline. A central objective is to use this case study to queer discourses of urban decline by considering how heteronormativity was involved in the construction of the city’s sexual margins in the post-World War II period. A related objective is to call into question the narrative of “decline” itself by providing one example of the opportunities it created for queer place-making.